IDENTITY AND TEMPORAL PERSPECTIVE OF ADOLESCENTS WITH HIGH ACHIEVEMENTS IN SCHOOL - Alipieva, Denitsa (Journal of Education Culture and Society, 2020)
The current article is an empirical approach reviewing the theories for the factors for formation of identity and self-conception in the adolescent. Under the theories for internal attribution and temporal perspective the study was conducted with teenagers between 11 and 18 years with different achievements. The aim is to show the relevance between the subjective affective involving and success in academic activity and realistic self-esteem that could enhance the abilities of students to create adequate plans and goals for future and mature self-conception.